Results-Based Aid in the Energy Sector : An Analytical Guide - Vivid Economics; Savedoff, William (World Bank Group, Washington, DC, 2015)
Results-based approaches (RBA) are becoming increasingly important, in both developed and developing countries. Within the energy sector, there are already several large-scale results-based schemes that make payments to implementers and service providers. However, support to national or regional governments based on the achievement of results in the energy sector remains unusual. This report seeks to explore the opportunity of utilizing RBA within the energy sector. It complements earlier work by vivid economics and the energy sector management assistance program (ESMAP) on results-based financing (RBF). The report constitutes one output in a broader research agenda on RBAs in the energy sector being undertaken by ESMAP of the World Bank. This report is intended to provide a high-level guide to results-based aid in the energy sector. It should be useful for a wide range of interested parties, including recipients, donor agencies, development practitioners, and academics. By providing a clear and justified analytical framework, the report ensures that the analysis is rigorous and open to critique. Chapter one gives introduction. Chapter two considers the theory of change underlying results-based aid, and uses this to derive four pre-conditions for RBA to be effective. Chapter three provides a discussion of the energy results chain, which can be used to frame the selection of results level and indicator. Chapter four outlines the factors to consider when selecting a results level and indicator for RBA. Chapter five considers when it is appropriate to target governments as the recipient in an aid program, rather than implementers or service providers. Chapter six discusses the remaining key design issues within an RBA agreement. A final section, chapter seven, considers the intersection between RBA and ongoing work on tracking and measuring energy access under the sustainable energy for all initiative.